Analysis of spin-up and spring back loads of landing gear based on slip rate - WU Ming; NIE Hong; ZHANG Ming; SHI Xiazheng (Hangkong gongcheng jinzhan)
The landing gear spin-up and spring back loads are the important part of the aircraft landing load. In order to effectively analyze the spin-up and spring back loads of the landing gear in the preliminary design stage，the two-wheel strut landing gear drop test dynamic model is established by using the nonlinear spring damping system at the center of the landing gear axle to simulate the strut elasticity，and the spin-up and spring back loads and its corresponding slip rate under the landing gear drop test of wheel reversal and actual aircraft landing are analyzed. The effects of aircraft heading velocity，runway slip rate curve and wheel pre-rotation angular velocity on landing gear spin-up and spring back loads are analyzed. The results show that the landing gear drop test simulation results of wheel reversal and actual aircraft landing are similar and consistent；reducing the heading velocity of the aircraft， giving the wheel pre-rotation angular velocity and reducing the friction coefficient between the tire and the ground can reduce the spin-up loads.